Identification des communautés anglophones du Québec : approche populationnelle dans le cadre de l’évaluation des disparités de santé associées à l’infarctus du myocarde - Drouin, Catherine; Courteau, Josiane; Orzanco, Maria Gabriela; Leroux, Denis; Vanasse, Alain (Revue d’études des Cantons-de-l’Est, 2011)
Il existe peu de données probantes permettant d’évaluer les disparités en matière de santé entre les groupes linguistiques au Québec. Ce projet propose une méthode de classification des communautés du Québec en fonction de l’appartenance linguistique de la population ainsi que l’association, basée sur le lieu de résidence des patients, des données médico-administratives et de celles du recensement. Ensuite, des comparaisons entre les groupes linguistiques quant aux traitements et au suivi des cas d’infarctus du myocarde, réalisées à l’aide de tests du Khi carré, permettent d’identifier que la principale disparité se manifeste dans les taux de revascularisation.

Exploring the determinants of language barriers in health care (LBHC): Toward a research agenda for the language sciences - Segalowitz, Norman; Kehayia, Eva (The Canadian Modern Language Review, 2011)
There is growing interest in language barriers in health care (LBHC) – interest, that is, in how the quality of health care service delivery might be compromised when patients and health care providers do not share the same first language. This article discusses LBHC as an emerging research area that provides valuable opportunities for researchers in various branches of the language sciences – including, among others, applied linguistics, theoretical linguistics, psycholinguistics, second language acquisition – to conduct basic research and to make contributions to the socially important area of medical communication. This article also proposes a research agenda aimed at attracting general language researchers to the study of LBHC, an agenda that is theory driven, programmatic, problem-solving oriented, and interdisciplinary in scope. In proposing this agenda, selected examples have been reviewed from the current literature that can serve as illustrative models for how future research into LBHC can proceed.